Effect of irrigation and fertilization on yield and tuber quality of winter potato in Erhai Lake basin - CHEN Zhiying; ZHANG Liudong; CHEN Lihong; YANG Wenjie; HU Yi (Guan'gai paishui xuebao)
【Objective】The growth of winter potatoes in Yunnan Province requires both irrigation and fertilization. This study examines the effects of irrigation amount and base-to-topdressing fertilization ratio on the growth, yield, and tuber quality of potatoes grown under full mulch conditions in the Erhai Lake basin. 【Method】A field experiment was conducted with two irrigation treatments, by maintaining the soil water content in the root zone at 80%-100% of field capacity (W1) and 64%-80% of field capacity (W2). Each irrigation treatment had two fertilizations with the fertilizers divided between base fertilization and topdressing at ratios of 1∶1 (T1) and 2∶1 (T2). The control treatment did not receive irrigation and fertilization. During the experiment, plant growth traits, yield, and tuber quality were measured.【Result】During the tuber expansion stage, irrigation significantly influenced root length, leaf area index (LAI), and dry matter accumulation (p＜0.05). The base-to-topdressing fertilization ratio also had a significant effect on root length and LAI (p＜0.05). The T1W1 combination resulted in the highest seedling emergence rate, LAI, yield, large tuber mass per ridge, and dry matter accumulation, producing a tuber yield of 46 657.70 kg/hm2, 7.59% to 22.15% higher than other treatments. The T2W1 combination yielded 43 367.20 kg/hm², ranking second. Both irrigation and the base-to-topdressing fertilization ratio significantly affected tuber yield (p＜0.05). The T1W1 combination also resulted in the highest starch content (149.87 mg/g fresh mass) and the lowest reducing sugar content (425.39 μg/g fresh mass). Tuber yield was positively correlated with both quality and the proportion of large tubers in the planting rows.【Conclusion】Considering growth, yield, and tuber quality, the T1W1 combination is optimal for winter potato production in the study area and similar regions with comparable soil and environmental conditions.